THE VALUE OF SERUM CREATININE AND CREATININE CLEARANCE IN CHRONIC LINER DISEASE - Esin ÖZYILKAN; Özgür Özyılkan; Yusuf BAYRAKTAR; Ilgar Taşdemir; Tülin ARAS; Serap ARSLAN; Burhan KAYHAN; Hasan TELATAR (Turkish Journal of Gastroenterology, 2020)
-